Clostridium difficile-Associated Diarrhea: clinical and epidemiological features - García Apac, Coralith (2018)
Introduction. Clostridium difficile-associated diarrhea (CDAD) is the major cause of nosocomial diarrhea in the industrialized world, and an outbreak has recently been reported there. The epidemiological features of CDAD have been poorly studied in developing countries. Our objective was to determine both clinical and epidemiological features of CDAD cases from Cayetano Heredia Hospital, and to review the literature.Methods. This is a case series including the first 50 patients with CDAD detected in a surveillance study of nosocomial diarrhea. We included patients older than 14 years who were hospitalized more than three days in medical and surgical wards from Cayetano Heredia Hospital receiving antibiotics. A CDAD case was suspected if the patient had three or more loose stools in the past 24 hours. The diagnosis was confirmed using an ELISA test for detecting C. difficile A and B toxins in stools.Results. Mean age of patients was 60.6 years (range, 16–91). Thirty of the 50 patients (60%) were male. The mean number of antibiotics used before diarrhea onset was 2.74 (range, 1–6). Most frequently used antibiotics were: clindamycin (38/50, 76%), ciprofloxacin (26/50, 52%) ceftazidime (19/50, 38%), and ceftriaxone (18/50, 36%). The mean hospitalization time before diarrhea onset was 11.9 days (range, 4–115). Other associated symptoms were: fever (15/50, 30%), abdominal pain (9/50, 18%), nausea (7/50, 14%), vomiting (5/50, 10%), and abdominal distention (4/50, 8%).Conclusion. CDAD is not and infrequent condition. It should be suspected in hospitalized patients receiving antibiotics, particularly clindamycin and cephalosporins.